Pengaruh Harga, Cita Rasa, dan Kualitas Pelayanan terhadap Niat Beli Ulang Konsumen Restoran Bakso Kadipolo di Surakarta - Nadea Rizki Widyastuti; Wuryaningsih Dwi Lestari (Economic Reviews Journal, 2024)
This research aims to examine the influence of price, taste and service quality on consumers' repurchase intentions at the Bakso Kadipolo restaurant in Surakarta. The population in this research is all consumers of the Bakso Kadipolo Restaurant in Surakarta. The sample used was consumers of the Bakso Kadipolo Restaurant who had previously purchased Bakso Kadipolo products in Surakarta, totaling 104 respondents. This research uses SPSS 23 to process data as well as being a tool in testing or analyzing data from research variables. The results of this research show that 1) the results of the first analysis show that price has a positive and significant effect on consumers' repurchase intentions at Bakso Kadipolo Restaurant, so the first hypothesis is declared accepted, 2) the results of the second analysis show that taste has a positive and insignificant effect on repurchase intentions consumers of the Bakso Kadipolo Restaurant in Surakarta, so the second hypothesis is declared rejected, 3) the results of the third analysis show that service quality has a positive and insignificant effect on the repurchase intention of consumers of the Bakso Kadipolo Restaurant in Surakarta, so the third hypothesis is declared rejected.